A BRIEF CASE HISTORY OF SANDHIGATA VATA MANAGED WITH AYURVEDA TREATMENT - Prasanna K.G; Arif Khan J.S; Gayathri R; Ann Rose P.A (International Journal of Applied Ayurved Research, 2017)
A 59 year old male patient of sandhigata vata came to ayurveda hospital with complaints of bilateral knee joint pain,tenderness,difficulty in walking with swelling,crackle sounds of the joints and warmth for 4 years but severe since 5 months. Patient increased the symptoms because of long standing and straining. Patient was treated as indoor patient for 21 days with internal medicines including maharasnadi kashayam , trayodasanga guggulu , ksheerabala tailam along with abhyagam , bandhanam and vasti therapy. Patient responded to the ayurvedic treatment .After the therapy patient felt improvement.